Metode Penyimpanan Bahan Baku Pastry & Bakery yang Meningkatkan Kualitas Layanan Hotel - Utami, Nisa Rahmaniyah; Ishak, Riani Prihatini; Faqih, Muhammad Ibnu Fiqhan (Stupa, 2022)
The department of food and beverage products is in charge of a section called pastry & bakery which provides a variety of cakes, breads and snacks that can be sold or enjoyed by guests. To maintain the quality of pastry & bakery products, one must do and pay attention to the storage of raw materials, one way is to do a good and correct storage method. This study aims to find out how the method used by R Hotel in an effort to maintain the quality of raw materials in the pastry & bakery section by describing what obstacles are experienced by the pastry & bakery section in storing raw materials. This study uses a qualitative method. The process of storing pastry & bakery raw materials at R Hotel uses predetermined standards. Like always checking the raw materials in the storage area, the placement of raw materials also needs to be considered in the storage process and implementing the FIFO (First In First Out) method.